O regime militar brasileiro visto desde Washington (1967-1978) - Caterina, Gianfranco (2012)
The aim of this study is to assess the delicate relationship between Brazil and the United States in a global scenario of détente between the two political-ideological blocs of Cold War. The superpower has, yet, as its main challenge the need to conciliate a search for its own interests as a nation, with ideals of democracy and respect for human rights. Brazil, on the other hand, was looking for prestige between powers, and more independence and autonomy on its foreign policy. In this process, it s possible to characterize, at least, three different overviews. First, a relative decline in U.S. power, political repression and high economic growth in Brazil. Second, oil international crisis, Watergate scandal, new military coups in South America, new human rights movements articulations and the beginning of abertura in Brazil. At last, the rise of Carter, and a dispute, on and off institutional level, on nuclear energy issues and human rights. I ll try to approach how the main political actors, the emergence of the human rights issue, and the constraints imposed by the international order have impacted on bilateral relations in the period from 1967 to 1978